The deteriorated microstructure characteristics of fly ash doped cementitious materials by dissolution. Issue 5 (September 2019) - Li, Xiang; Liu, Chunfeng; Lu, Chao; Peng, Ziling; Li, Jiazheng; Xingdong, LV
Abstract: The microstructure differentia of fly ash doped cementitious materials between before and after dissolution was observed by XRD and MIP to analyze the microstructural deterioration characteristics of different samples. Results showed that there were great changes in hydration products, cement clinker and fly ash particles after dissolution. Pore structure evolution during dissolution indicated that the effect of C-S-H decalcification on pore structure was not negligible and the traditional definition between the harmful pore and the harmless pore was not applicable.